Subcutaneous hydatid cyst - Ferreli, C... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1993)
The authors describe a case of subcutaneous hydatidosis in a 62-aear-old women. The cyst appeared in the right lumbar region as an elastic nodule of about 3 cm diameter. The overlying skin appeared normal. Histologically in the deep dermis and in the subcutis multiple isolated cystic formations of different sizes composed of an intensely PAS positive wall of concentric lamellar structure were present. The inner surface showed small nuclei immersed in a granulous cytoplasmatic mass. Within this cystic cyvity daughter cysts and scolices were observed. Thorough examinations failed to reveal involvement of other organs.
Keywords: Echinococcosis; Lumbosacral region; Pathology; Ultrastructure